Pengembangan Instrumen Tes Untuk Mengukur Ketepatan Pukulan Ke Target Dalam Olahraga Softball: (Development of Test Instruments to Measure Accuracy Beat to The Targets in Softball Sports) - Khairurraziqin Khairurraziqin; Abdul Haris Handoko (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2020)
Softball was originally a branch of sports games played by nine players with different positions and abilities, softball in Indonesia has only been developing for several decades. This research aims to find out how the development of test instruments to measure the accuracy of punches to targets in softball sports. This research is a research and development (research and development), which means this research is a product-oriented research. The development of this test is carried out through stages: preliminary, developing, carrying out product development, product evaluation, and the final results in the form of a manual test of accuracy of punches to the target in softball sports. Data is collected through tests, questionnaires and interviews. The data is in the form of assessment results concerning product bags, suggestions for improvement, as well as other qualitative data. Quantitative data were analyzed with descriptive statistics. The suggestions obtained are used to revise the product. The results of the product quality assessment of the development of the accuracy of the hit to target test in softball are very decent with an average score of 4.7, and the average percentage score of 94%. The validity and reliability of the test obtained from the trial results is the validity of